Words are Physicians for an Ailing mind For Andrzej Boguslawski on the Occasion of his 60th Birthday - Grochowski, Maciej; Weiss, Daniel (Sagners Slavistische Sammlung, 1991)
The contributions included in the present volume cover a large number of various linguistic disciplines: the topics range from philosophy of language, pragmatics, semantics and syntax to morphology and phonology, and even language history, translation theory and quantitative linguistics figure among them. This astonishing abundance of different research objects and methods sheds some light on the universality of interests which characterize the scholar to whom this volume is dedicated.